PENDIDIKAN KEWARGANEGARAAN (PKn) SEBAGAI WAHANA PENDIDIKAN DEMOKRASI DALAM MEWUJUDKAN SMART AND GOOD CITIZEN - Mufidah, Nastiti (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2020)
Abstract: The purpose of this paper is to review democratic education which is then constructed in an analysis in which it is revealed about how citizenship education as a vehicle for democratic education in an effort to realize smart and good citizens. The writing of this article is a descriptive explanatory type of writing that explains the urgency of constructing the role of citizenship education as a vehicle for democratic education in realizing smart and good citizens. This writing uses the method of literature study which is a method that bases on various media as a source of literature relating to civic education, democratic education and various efforts in realizing smart and good citizens. The analysis based on the findings concludes that democratic education must become an integrated education with all aspects of citizens' lives in order to be able to build a political awareness of society holistically. Citizenship education with the principle of "nation and character building" is a vehicle for the implementation of representative democratic education in which democracy is taught with the framework of nationality and nationality in building "smart and good citizens" as a form of democratic citizenship. Abstrak: Tujuan penulisan ini yakni mengulas pendidikan demokrasi yang kemudian dikonstruksi dalam analisis yang didalamnya terungkap tentang bagaimanakah pendidikan kewarganegaraan sebagai wahana pendidikan demokrasi dalam upaya mewujudkan smart and good citizen. Penulisan artikel ini merupakan jenis penulisan Deskriptif Eksplanatif yaitu memaparkan urgensitas pengkontruksian peran pendidikan kewarganegaraan sebagai wahana pendidikan demokrasi dalam mewujudkan smart and good citizen. Penulisan ini menggunakan metode studi literatur yakni metode yang mendasarkan pada berbagai media sebagai sumber literatur yang berkaitan dengan pendidikan kewarganegaraan, pendidikan demokrasi serta berbagai upaya dalam mewujudkan smart and good citizen. Hasil analisis yang berdasarkan hasil temuan memberikan kesimpulan bahwa pendidikan demokrasi harus menjadi pendidikan yang terintegrasi dengan seluruh aspek kehidupan warganegara agar mampu membangun kesadaran politik masyarakat secara holistic. Pendidikan kewarganegaraan dengan prinsip “nation and character building” merupakan wahana implementasi pendidikan demokrasi yang representatif dimana demokrasi diajarkan dengan framework kenegaraan dan kebangsaan dalam membangun “smart and good citizent” sebagai wujud warganegara yang demokratis.